Effectiveness of algorithm visualisation in studying complex algorithms: a case study using TRAKLA Ravie / Chandren Muniyandi, Ali Maroosi - Muniyandi, Chandren; Maroosi, Ali (Penerbit UiTM (UiTM Press), 2015)
Algorithm visualisation (AV) can be utilised to improve students ’programming and programme comprehension skills. Visual tools motivate students and teachers to more effectively study or teach complex algorithms. This study demonstrates that AV tools significantly improve student skills and scores and enhance understanding of complex algorithms to a degree greater than those of less complexity. TRAKLA2 is a visualisation tool used to enhance the process of learning algorithm construction and optimization. To assess the effectiveness of TRAKLA2, students were given an algorithm test prior to being introduced to the software. Students then used TRAKLA2to learn five different types of algorithms. Analysis of students’ feedback from questionnaires and tests showed greater levels of improvement in understanding complex problems as compared to those of less complexity.